Examining the succession process in family businesses: A case study of a catering business - Raki Zikra Refli; Grisna Anggadwita; Sucheta Agarwal (Jurnal Fokus Manajemen Bisnis, 2026)
This study explores succession planning to ensure the long-term sustainability of family businesses, a critical issue given the high failure rate linked to ineffective leadership transitions. Focusing on Sedap Catering, a family business established in 1987 in Bandung, West Java, Indonesia, the research aims to analyze the stages and dynamics of succession, specifically how the founding generation applies strategies to potential successors. Family businesses are crucial to the Indonesian economy, but they often face challenges in maintaining leadership continuity. Theoretical frameworks include family business theory, succession planning, and stewardship theory, offering insights into the motivations of family leaders during the succession process. A qualitative approach is used with a single case study, involving in-depth interviews, observations, and document studies. Five key respondents were selected through purposive sampling. Data analysis is conducted using thematic analysis, triangulation, and member checking to ensure reliability. The results show that Sedap Catering’s succession process is informal yet structured, reflecting the family’s values of trust, continuity, and service quality. Successors are selected based on character, competence, and commitment, with gradual integration into the business and continuous evaluation. This method ensures smooth leadership transfer, strong employee loyalty, and family harmony. The study provides practical insights for family businesses in Indonesia and contributes to academic understanding of succession planning.